Necrotising Fasciitis of the Lower Limb caused by Community-Acquired Methicillin-Resistant Staphylococcus aureus - Chan, C.K.; Merican, A.M.; Nawar, A.M.; Hanifah, Y.A.; Thong, Kwai Lin (Malaysian Orthopaedic Association (MOA), 2010)
Necrotising fasciitis caused by Community-Acquired Methicillin-resistant Staphylococcus aureus (CA-MRSA) has emerged as a new entity. Although it is recognised worldwide, there have been no reported cases to date in Malaysia. We report a case of necrotising fasciitis of the left lower limb in an otherwise healthy 20-year-old man. He presented with septic shock and despite the paucity of clinical signs in the limb, the infection was aggressive. Methicillin-Resistant Staphylococcus aureus (MRSA) was isolated from the deep fascia of the leg. Panton-Valentine leucocidin gene (PVL), which is a stable genetic marker for CA-MRSA strain, was positive in this case. This case of community acquired MRSA necrotising fasciitis is of concern and may herald the emergence of this resistant organism in Malaysia. Vigilant surveillance and microbiological monitoring is needed to follow this CAMRSA trend.